مدى استجابة مشروع المحاسبة العمومية من المعايير المحاسبية الدولية في القطاع العام Ipsas - بوعكاز, سميرة (جامعة الوادي - University of Eloued, 2023)
This study aims to find out the extent to which the international public accounting project in the public sector IPSAS is responsive by highlighting the first international standard IPSAS01 and what it includes as a minimum for the requirements of the four financial statements (the list of cash flows, the list of financial performance, the list of financial position, the list of changes in capital , the appendices) recommended for comparison with the actual items presented by the Public Accounting Standards project in Algeria where this study discussed the aspects of public accounting in Algeria as well as the international accounting standards in the public sector IPSAS. The international standards by dropping the content of a financial list included by the latter with what came to the modernization project. The study concluded that the initial accounting standards project in Algeria has responded to some extent with what was recommended by the IPSAS international standard in terms of content and in line with what the current Algerian economic environment imposes. the public sector.
IPSAS The extent to which the public accounting project responds to the international accounting standards in the public sector in Algeria (IPSAS).
مقال
Keywords: المحاسبة العمومية ; المعايير المحاسبية الدولية ; القطاع العام ; الرقابة المالية; public accounting, international accouwdnting standards, public sector, financial control